Representation of Javanese Ideology in Riri Riza’s OPPO Film - Ahmad Toni (Departemen Ilmu Komunikasi FISIP Universitas Atma Jaya Yogyakarta, 2025)
The research findings reveal that: (1) at the text level, the representation is conveyed through six signs of low-angle shooting techniques using an Oppo smartphone camera, challenging male ideological dominance in Javanese, European, and Chinese patriarchal ideologies; (2) at the praxis discourse level, the film's production system reflects the generational shift in perception, particularly among Generation Z, within the smartphone content industry; (3) at the discourse context level, it serves as Oppo Indonesia's marketing communication strategy to target the male segment, which is significant in the Indonesian smartphone content industry.